1997
DOI: 10.1074/jbc.272.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a Novel Phospholipase A2 from Bovine Seminal Plasma

Abstract: Phospholipases A2 are enzymes believed to play important roles in numerous physiological systems including sperm cell maturation. Relatively little work has, however, been devoted to study these enzymes in seminal plasma. We therefore undertook the purification and characterization of this enzyme from bovine seminal plasma. After a 330-fold purification, an activity corresponding to a protein of 100 kDa was identified by gel filtration. SDS-polyacrylamide gel electrophoresis analysis of the purified fraction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…The mechanism by which this effect occurred is not clear, because gossypol inhibits endothelium-dependent relaxation factor-mediated relaxation (Radermacher et al, 1990), lipoxygenase (Kulkarni and Sajan, 1997), phospholipase A 2 (Soubeyrand et al, 1997), protein kinase C (Pelosin et al, 1990), gap junctions (Ye et al, 1990), and Ca 2ϩ chan- nels (Sgaragli et al, 1993;Bai and Shi, 2002). Of relevant importance, gossypol inhibits channels and transporters that are involved in cell volume regulation, i.e., taurine channels (Ballatori et al, 1995), myo-inositol uptake (Strange et al, 1993) and volume-activated Cl Ϫ channels that are also sensitive to 4,4Ј-diisothiocyano-2,2Ј-stilbene disulfonate (Gschwentner et al, 1996;Szucs et al, 1996), an agent that blocks EpDRF-induced relaxation .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which this effect occurred is not clear, because gossypol inhibits endothelium-dependent relaxation factor-mediated relaxation (Radermacher et al, 1990), lipoxygenase (Kulkarni and Sajan, 1997), phospholipase A 2 (Soubeyrand et al, 1997), protein kinase C (Pelosin et al, 1990), gap junctions (Ye et al, 1990), and Ca 2ϩ chan- nels (Sgaragli et al, 1993;Bai and Shi, 2002). Of relevant importance, gossypol inhibits channels and transporters that are involved in cell volume regulation, i.e., taurine channels (Ballatori et al, 1995), myo-inositol uptake (Strange et al, 1993) and volume-activated Cl Ϫ channels that are also sensitive to 4,4Ј-diisothiocyano-2,2Ј-stilbene disulfonate (Gschwentner et al, 1996;Szucs et al, 1996), an agent that blocks EpDRF-induced relaxation .…”
Section: Discussionmentioning
confidence: 99%
“…In mouse testis, sPLA 2 -IIC is expressed mainly in spermatocytes and spermatids undergoing meiosis (73). It would be of interest to test whether sPLA 2 -IIC has some function in the sperm acrosome reaction and the fusion of sperm and oocyte plasma membranes (74,75), in which PLA 2 is believed to play a key role. Cells undergoing apoptosis in such tissues are an attractive candidate for the sPLA 2 -IIC target, since we have recently shown that hydrolysis of apoptotic cell membranes by sPLA 2 -IIA does not require anchoring to proteoglycans on the plasma membranes (76).…”
Section: Discussionmentioning
confidence: 99%
“…PLA2 has also been found on the plasma membrane as well as in the acrosome and post-acrosomal substance of ejaculated bull sperm [84]. It has a molecular weight of 60 kDa and pI 5.6 [69] while an isoform 16 kDa PLA2 [62] has also been detected. It has been shown that PLA-2 is attached on the surface of ejaculated bull sperm but not on the epididymal sperm [61].…”
Section: Phospholipase A2mentioning
confidence: 99%